1995
DOI: 10.1029/95jb01424
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and geochronology of ancient southeast Indian and southwest Pacific seafloor

Abstract: Within the Australian‐Antarctic Discordance (AAD), a boundary exists between isotopically defined “Pacific‐type” and “Indian‐type” mid‐ocean ridge basalt (MORB) erupted along the Southeast Indian Ridge (SEIR). This boundary has migrated westward beneath the easternmost AAD spreading segment at a minimum rate of 25 mm/yr since 4 Ma; however, its long‐term history remains a matter of speculation. To determine if Pacific‐type upper mantle has migrated westward beneath the eastern Indian Ocean basin as Australia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 86 publications
2
71
0
Order By: Relevance
“…Although the nature and age of oceanic crust in the Tasman Sea is well demonstrated by magnetic anomalies, basement has only been sampled at DSDP Site 283, southeast of Tasmania (Pyle et al 1995). To our knowledge, there is no information on dredged rocks from the floor of the New Caledonia Basin.…”
Section: Geological Recordmentioning
confidence: 99%
“…Although the nature and age of oceanic crust in the Tasman Sea is well demonstrated by magnetic anomalies, basement has only been sampled at DSDP Site 283, southeast of Tasmania (Pyle et al 1995). To our knowledge, there is no information on dredged rocks from the floor of the New Caledonia Basin.…”
Section: Geological Recordmentioning
confidence: 99%
“…Isostatic a/'guments generally fall within the range of 85 ø to 150øC [Hayes, 1988 [1990,1991] suggested that the upper mantle beneath the axis of the SEIR is currently downwelling beneath the AAD, based upon the The unusual geophysical features of the AAD and surrounding SEIR are associated with a sharp discontinuity in the Sr, Nd, and Pb isotopic signatures of SEIR lavas. This marks the boundary between "Indian" and "Pacific" mid-ocean ridge basalt (MORB) source upper mantle provinces [Klein et al, 1988;Pyle et al, 1992Pyle et al, , 1995. This transition in isotopic signature is presently located near a transform offset of the SEIR between 126.5 ø and 127øE and extends over less than about 70 km along axis [Pyle et al, 1992].…”
mentioning
confidence: 99%
“…Off-axis samples dredged from 3-4 Ma seafloor in the easternmost AAD spreading segment record the presence of Indian MORB mantle beneath a segment that is now erupting lavas with Pacific type isotopic characteristics [Pyle et al, 1992]. This change in mantle source signature implies that Pacific mantle has migrated westward beneath the easternmost AAD spreading segment at a minimum rate of 25 mm yr-1 for the last 3-4 Myr [Pyle et al, 1992[Pyle et al, , 1995 Although the off-axis data described above are not conclusive [Pyle et al, 1995] …”
mentioning
confidence: 99%
“…It also indicated an island arc setting but with higher probability of about 63 % followed by 37 % for the continental arc (Table S50). Pyle et al (1995) reported geochemical data from fresh as well as altered seafloor rocks (dredged and drilled) of different ages (0-4 and 15-23 Ma; Table S13). The presence of micaceous alteration minerals, low CaO/Al 2 O 3 reflecting pervasive alteration, unusually high Rb contents, and contamination from seawater alteration were suggested by Pyle et al (1995) as the symptoms of alteration for most samples.…”
Section: Test Study A4: Moyuta and Tecuamburro Volcanoes Guatemalamentioning
confidence: 99%
“…Pyle et al (1995) reported geochemical data from fresh as well as altered seafloor rocks (dredged and drilled) of different ages (0-4 and 15-23 Ma; Table S13). The presence of micaceous alteration minerals, low CaO/Al 2 O 3 reflecting pervasive alteration, unusually high Rb contents, and contamination from seawater alteration were suggested by Pyle et al (1995) as the symptoms of alteration for most samples. The authors used an intense leaching procedure before sample preparation for geochemical data acquisition.…”
Section: Test Study A4: Moyuta and Tecuamburro Volcanoes Guatemalamentioning
confidence: 99%